Chemical Composition and Antibacterial Activity of Red Murta (Ugni Molinae Turcz.) Seeds: An Undervalued Chilean Resource - Wilkens-Anwandter, M (Springer, 2020)
Murta (Ugni molinae Turcz) is an endemic Chilean specie mostly used in medical, cosmetic, and food industries. However, during the industrial processing of murta fruits, the biomass containing the seeds is discarded as an industrial byproduct that does not find significant uses yet. This work is a first approach to valorize murta biomass through the identification and quantification of principal chemical constituents and exploring their antibacterial properties. The proximal analysis revealed that murta seeds exhibited significant content of raw fiber (64%), crude fat (14%), crude protein (12%), and low levels of ashes (1.5%) and minerals (0.04–0.23%). Dietary fiber was mainly composed of lignin, cellulose, pectin, and hemicellulose. Polyunsaturated fatty acids (89.0%), monounsaturated fatty acids (7.7%), and saturated fatty acids (3.3%) were the main constituents of seed oils. The arginine, asparagine, glutamic acid, and glycine were the primary protein constituent amino acids. Tannin fractions, total polyphenolic content, and oxygen radical absorbance capacity as antioxidant activity were measured. The chromatographic and mass spectrometric analysis (HPLC–MS/MS) confirmed the presence of several phenolic compounds like phenolic acids, flavonols, flavones, proanthocyanidins, and high molecular weight polyphenols. The murta seed extract showed high antibacterial activity against both Gram positive (Staphylococcus aureus, Bacillus cereus, and Streptococcus pyogenes) and Gram negative (Escherichia coli, Salmonella typhi, and Pseudomonas aeruginosa) bacterial strains. Murta seeds could be considered as a new source of nutritional components and bioactive compounds for different nutraceutical and food applications. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.